The Determinan Kinerja Keuangan Perusahaan Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia - Jusmarni Amir (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
Stocks are currently a popular investment product among investors. Stocks that are of interest to investors are stocks that have a high selling value because the stock price is a very important factor to pay attention to and indicators are used to measure the welfare of shareholders. The higher the share price, the higher the value of the company and vice versa. However, investing in stocks in the capital market is also filled with an element of uncertainty or risk, this is because investors do not know with certainty the results they will get from their investments. Company specific financial information is one of the important internal company factors that can influence investors to invest. The research aims to analyse the effect of Capital Structure, liquidity, and profitability on stock price. Samples used in this study are food and beverage companies listed in the Indonesian Stock Exchange during 2016-2018 periods. Multiple linear regression method used to anlyse the effect of DER,CAR, and NPM on Stock Price. The results showed that DER and CAR have not significant effect on Stock Price. NPM have a significant effect on Stock Price. Keywords: Capital Structure, liquidity, Profitability, Stock Price